Child Abuse Recognition Training for Prehospital Providers Using Deliberate Practice. (2nd November 2021) - Adelgais, Kathleen; Pusic, Martin; Abdoo, Denise; Caffrey, Sean; Snyder, Katherine; Alletag, Michelle; Balakas, Ashley; Givens, Timothy; Kane, Ian; Mandt, Maria; Roswell, Kelley; Saunders, Mary; et al.
Abstract: Background: In most states, prehospital professionals (PHPs) are mandated reporters of suspected abuse but cite a lack of training as a challenge to recognizing and reporting physical abuse. We developed a learning platform for the visual diagnosis of pediatric abusive versus non-abusive burn and bruise injuries and examined the amount and rate of skill acquisition. Methods: This was a prospective cross-sectional study of PHPs participating in an online educational intervention containing 114 case vignettes. PHPs indicated whether they believed a case was concerning for abuse and would report a case to child protection services. Participants received feedback after submitting a response, permitting deliberate practice of the cases. We describe learning curves, overall accuracy, sensitivity (diagnosis of abusive injuries) and specificity (diagnosis of non-abusive injuries) to determine the amount of learning. We performed multivariable regression analysis to identify specific demographic and case variables associated with a correct case interpretation. After completing the educational intervention, PHPs completed a self-efficacy survey on perceived gains in their ability to recognize cutaneous signs of abuse and report to social services. Results: We enrolled 253 PHPs who completed all the cases; 158 (63.6%) emergency medical technicians (EMT), 95 (36.4%) advanced EMT and paramedics. Learning curves demonstrated that, with one exception, there was an increase in learning for participants throughout the educational intervention. Mean diagnostic accuracy increased by 4.9% (95% CI 3.2, 6.7), and the mean final diagnostic accuracy, sensitivity, and specificity were 82.1%, 75.4%, and 85.2%, respectively. There was an increased odds of getting a case correct for bruise versus burn cases (OR = 1.4; 95% CI 1.3, 1.5); if the PHP was an Advanced EMT/Paramedic (OR = 1.3; 95% CI 1.1, 1.4) ; and, if the learner indicated prior training in child abuse (OR = 1.2; 95% CI 1.0, 1.3). Learners indicated increased comfort in knowing which cases should be reported and interpreting exams in children with cutaneous injuries with a median Likert score of 5 out of 6 (IQR 5, 6). Conclusion: An online module utilizing deliberate practice led to measurable skill improvement among PHPs for differentiating abusive from non-abusive burn and bruise injuries.